A reconsideration of the northeastern building at Pylos: evidence for a Mycenaean redistributive center - Bendall, L (Archaeological Institute of America, 2003)
The Northeastern Building at the Mycenaean palace of Pylost has long been interpreted as a workshop. The present study argues that this was not the building's function. Using both the archaeological and Linear B data, it is argued that the building was instead a "clearinghouse" or "redistributive center" for goods and personnel, similar to the function recently suggested by C. W. Shelmerdine for the West House Group at Mycenae. It was a major storage complex and above all and administrative center, working in close association with the central Pylian Archives Complex. The article examines first the archaeological evidence. Finds thought to support the workshop hypothesis, such as chisels, knives, and obsidian flakes, are compared with distributions of such artifacts throughout the palace. It is suggested that the archaeological material alone indicates nothing for the Northeastern Building beyond administration and storage, especially of weaponry. Next the documents and sealings are examined in the context of the wider Pylian administrative system. Finally, the documents are considered individually, and it is argued that they are not "workshop" documents, but concern movement of goods and resource management. It is concluded that nothing from the building suggests on-site production, but numerous factors point to a redistributive center - a clearinghouse for goods entering the palace complex as a whole.